Endogenous Market Participation and the General Equilibrium Value of Money - Chatterjee, Satyajit; Corbae, Dean (Journal of Political Economy, 1992)
We study the monetary theory implications of fixed costs associated with trade in private assets. We show that with heterogeneous endowment profiles it is possible for an endogenous subset of agents to hold currency even when it is dominated in return by a competing asset. With respect to positive issues in monetary theory, the model implies that changes in the steady-state growth rate of the money supply have a negative effect on real interest rates because of endogenous market participation measures. On the normative side, we show that there may be an equity-efficiency trade-off from monetary deflation.